Análise do impacto dos requisitos arquivísticos para a produção de documentos arquivísticos digitais nos sistemas de informação de negócio - Marcelo Lacerda Garcia (2024)
Digital Information and Communication Technologies (DICTs) have experienced significant advancement since the emergence of the Internet, particularly since the 1990s. Society – individuals, businesses, and governments – is increasingly integrated with and reliant on DICTs. New sciences are emerging, and there is a challenge to provide DICTs with more resources to meet society's needs. Considering the records of activities performed by individuals within the computerized environment, we observe an increasingly irreversible transition from the use of electronic media for informational records, to the detriment of paper-based media. For records in electronic media, although they may be abundant, we may encounter issues of authenticity and reliability of these records, and even of information recorded in obsolete technologies, despite their relatively recent production. In the face of this scenario of technological evolution, there is a perceived need, beyond granting greater longevity to electronic records, to take measures to preserve their authenticity and reliability. Among various initiatives worldwide, emerges in Brazil, supported by the National Archives Council (CONARQ), the Model Requirements for Electronic Records Management Systems – e-ARQ Brasil. As specified in the document titled e-ARQ Brasil of May 2022, e-ARQ Brasil establishes minimum requirements for an Electronic Records Management System (ERMS), regardless of the technological platform on which it is developed and/or implemented. It provides detailed functional and non-functional requirements that an electronic records management system must meet. These requirements are understood as fundamental to address the issue of preservation, authenticity, and reliability of electronic records. It is understood that it is not about transforming every business system into an ERMS, but rather to simply adapt it to produce electronic records that favor records management conducted by an ERMS. This research aims to gather information on the requirements necessary to be implemented in business systems to produce electronic records. This study conducted a practical analysis of its considerations, investigating the process by which the SiGA system of UFMG (Federal University of Minas Gerais) creates electronic records. The focus was on the production of Academic Transcript and Graduation Diploma.